Answer:
6 and -4
Step-by-step explanation:
a + b = 2
a - b = 10
Solve:
from the first eq.
a = 2 - b
replacing this value in the second eq.
(2-b) - b = 10
2 - 2b = 10
-2b = 10 - 2
-2b = 8
b = 8/-2
b = -4
from the second eq.
a - b = 10
a - (-4) = 10
a + 4 = 10
a = 10 - 4
a = 6
Check:
from the first eq.
6 + (-4) = 2
6 - 4 = 2
A. First you must start by plugging in your equation solve Y = 2(5) + 1 then you must simplify by solving your 2×5+ 1 and then you end up with Y equals 11
B. Again plug in your equation Y = 2(-5) + 1 then you must simplify by solving your 2×-5+ 1 and then you end up with Y equals -10+ one which simplifies to y = -9
I hope this helps
Answer:
You have 2 mystery boxes and you add them to 3 mystery bags. Each has a different amount of things represented by a and b.
Step-by-step explanation: